Effect of extraction, ratio, and solvent concentration on total flavonoid content and antioxidant activit of singkel (premna serratifolia linn.) using dpph method - Isnindar, Isnindar; Luliana, Sri; Zahid, Muhammad (Jurnal Teknosains, 2025)
Singkel (Premna serratifolia Linn.) is a medicinal plant commonly found in tropical regions, including Indonesia, which contains flavonoids, alkaloids, polyphenols, and triterpenoids. Flavonoids in singkel leaves act as antioxidants that can prevent oxidative stress, which is a causative factor of degenerative and chronic diseases such as cancer, arthritis, and cardiovascular diseases. This study aims to determine the effects of total flavonoid content and IC50 values in singkel leaves based on extraction methods, solvent concentration, and the ratio of extract to solvent. The methods used include maceration, soxhlet extraction, and Microwave-Assisted Extraction (MAE), with ethanol solvent concentrations of 60%, 70%, 80%, and 96%, and extract-to-solvent ratios of 1:10, 1:20, and 1:30. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method with UV-Vis spectrophotometry. The results showed that the soxhlet extraction method yielded the highest total flavonoid content of 24.56±1.81 mgQE/g with an IC50 value of 20.31±1.58 μg/mL. The 96% solvent concentration provided the best results with a total flavonoid content of 26.12±0.06 mgQE/g and an IC50 value of 15.51±2.17 μg/mL. In the solvent ratio testing, the 1:20 ratio showed the highest total flavonoid content of 19.37±0.5 mgQE/g, while the 1:10 ratio provided the best IC50 value of 11.99±1.02 μg/mL. In conclusion, the extraction method, solvent concentration, and solvent ratio significantly affect the flavonoid content and antioxidant activity of singkel leaves.